2017
DOI: 10.1089/thy.2017.0264
|View full text |Cite
|
Sign up to set email alerts
|

Automated MicroSPECT/MicroCT Image Analysis of the Mouse Thyroid Gland

Abstract: MicroSPECT/CT image acquisition and analysis for thyroidal RAI uptake is greatly improved by the cradle and the CTViewer software, respectively. Furthermore, the approach of superimposing thyroid VOIs from t24 images to select thyroid VOIs on corresponding aligned t1 images can be applied to studies in which the target tissue has differential radiotracer retention from surrounding tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In our study, scintigraphy data showed a decrease in Na 99m TcO 4 uptake in RAI-treated mice, which was more intense in the P glands. These results are in agreement with the literature [41] and the TUNEL data, showing that the P glands were more radiosensitive than the SM glands since the former are composed almost entirely of serous cells [42]. Despite the attempt of glandular stimulation, the administration of lemon was not able to alter Na 99m TcO 4 excretion, probably due to swallowing alterations and a reduction in the lemon stimulation induced by the anesthetic agent [43].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, scintigraphy data showed a decrease in Na 99m TcO 4 uptake in RAI-treated mice, which was more intense in the P glands. These results are in agreement with the literature [41] and the TUNEL data, showing that the P glands were more radiosensitive than the SM glands since the former are composed almost entirely of serous cells [42]. Despite the attempt of glandular stimulation, the administration of lemon was not able to alter Na 99m TcO 4 excretion, probably due to swallowing alterations and a reduction in the lemon stimulation induced by the anesthetic agent [43].…”
Section: Discussionsupporting
confidence: 91%